2020
DOI: 10.12669/pjms.36.covid19-s4.2660
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of CoViD-19 Pandemic: Recovery and mortality ratio around the globe

Abstract: Coronavirus Disease 2019 (CoViD-19) is the third type of coronavirus disease after severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) that appears in human population from the past two decades. It is highly contagious and rapidly spread in the human population and compelled global public health institutions on high alert. Due to genetic similarity of this novel coronavirus 2019 with bat virus its emergence from bat to humans is possible. The virus survive in the droplets of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…Mortality rate in our study was higher than the reported rate for the UAE due to the fact that our study analyzed only those with diabetes [21]. This was in concordance with a meta-analysis done by Kumar et al [22], which analyzed 33 studies.…”
Section: Discussionsupporting
confidence: 91%
“…Mortality rate in our study was higher than the reported rate for the UAE due to the fact that our study analyzed only those with diabetes [21]. This was in concordance with a meta-analysis done by Kumar et al [22], which analyzed 33 studies.…”
Section: Discussionsupporting
confidence: 91%
“…The thyroid gland is a major organ in maintaining many long term functions of the body, in particular, cardiovascular, respiratory, and catabolic tasks, which is why many lower-income countries have implemented salt iodination as a way to counter the consequences of iodine-deficient thyroid disorders [ 8 , 9 ]. As an emerging disease, COVID-19 has taken a devastating toll in lower-middle-income countries, with seemingly no end in sight to the rising death toll which, at the time of this writing, stands to cross more than 1, 000, 000 [ 10 ]. As the pandemic rages on, more and more insights are emerging into not just the multi-systemic involvement of the virus, but its impact on disrupting the endocrine system—with more long-term effects—can also no longer be overlooked, particularly in the context of countries already struggling with prevalent endocrine diseases [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 The pandemic has led to increased COVID-19 morbidity and mortality. 3 As of October 2, 2020, more than 34.6 million cases and one million deaths were reported globally. 4 The pandemic has also had devastating effects on the world’s economy with collapse of many businesses and loss of many jobs.…”
Section: Introductionmentioning
confidence: 99%